A Qualitative Assessment of Tan Chong Motor’s Entry Into Vietnam: A Case Study - Ong, Justin Yi Yu (2013)
The aim of this thesis is to perform a qualitative case study on Tan Chong Motor, a Malaysian automotive conglomerate that began from being a distributor to Nissan Motor Company, as they execute Indo-China expansion plan by first penetrating into Vietnam in 2011, an emerging country that recently begun attracting Foreign Direct Investments by restructuring regulations and infrastructures. This thesis will take into study the literature on internationalization, FDI, and institutional challenges of operating in ‘South countries’ to form a framework that will then be used to assess Tan Chong Motor’s move into Vietnam. The ‘CaStER’ framework integrates four variables of Internationalisation, FDI, and cultural challenges to assess a venture of a company; Capital assessment, Structural assessment, mode of Entry analysis, and assessment of market Risk. Using ‘CaStER’, the study will firstly assess Tan Chong’s penetration to the Vietnam market. Adding value, this thesis will then assess Tan Chong Motor’s plans to duplicate the penetration method to Myanmar which in 2012 has become the next frontier-wonder after Vietnam, as is aligned with Tan Chong Motor’s Indo-China expansion plan. The study finds that with the pursuit of first mover’s advantage, it is also important to assess reservations on critical capital capacity to determine the manner and timing of penetration. This study also features a review of an interview segment series, ‘Insight Vietnam’, which discusses about Vietnam, its attractants and challenges as an emerging market attempting to attract FDI to modernize and develop the country through a panel of investors and consultants who have experience with the market.